Hybrid PO-MoM analysis of large axi-symmetric radomes. - Moneum, M.A.A.
Over the last three decades, intensive work has been done to develop techniques aimed at accurate and efficient analysis of antenna radome systems. Some applications involve radar operating in the millimeter wave range and for those cases the radome size can be on the order of one hundred wavelengths or so in length. For practical simulations of such large radomes, a hybrid physical optics-method of moments (PO-MoM) technique is presented for accurate and efficient analysis of electrically large radomes. The procedure combines the method of moments (MoM) for modeling the tip region of the dielectric radome and ray optics in conjunction with physical optics (PO) for treating the flatter smooth section of the radome. Calculated far-field patterns using the new technique agree well with measured data for a reflector antenna radiating in the presence of a large radome. The computational time for simulating the performance of a 46λ reflector in the presence of an 88λ long radome was a mere 4 h on a 233 MHz PC
Keywords: Antenna radome systems; Computational time; Dielectric radome; Electrically large radomes; Far-field patterns; Hybrid PO-MoM analysis; Hybrid physical optics-method of moments; Integral equations; Large axi-symmetric radomes; Millimeter wave radar; Radome size; Ray optics; Reflector antenna; Simulations; Tip region